Profil Kemampuan Pemecahan Masalah Siswa SMA pada Materi Fluida Statis - Ernila Siringo Ringo; Sentot Kusairi; Eny Latifah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This research was aimed to analyze the profile of students' ability to solve static fluid problems. The survey research involved 70 XII students of Malang State High School 4. The research instrument was in the form of three problem solving questions in the form of a description. The results showed the percentage of students in the expert category was still low at 31% and students in the novice category were quite high at 69%, so that students' overall problem solving abilities were classified as low. In this study, a number of student difficulties were still found, one of which was about the magnitude that affected the buoyancy force of objects in the fluid primarily on the problems of Archimedes' Law. Innovative learning efforts are needed to improve students' ability to solve problems.Abstrak: Penelitian ini bertujuan untuk menganalisis profil kemampuan siswa dalam memecahkan permasalahan fluida statis. Penelitian survei ini melibatkan 70 siswa kelas XII SMA Negeri 4 Malang. Instrumen penelitian berupa tiga butir soal pemecahan masalah berbentuk uraian. Hasil penelitian menunjukkan persentase siswa kategori expert masih rendah yaitu sebesar 31% dan siswa kategori novice cukup tinggi sebesar 69%, sehingga kemampuan pemecahan masalah siswa secara keseluruhan tergolong rendah. Pada penelitian ini, beberapa kesulitan siswa masih ditemukan salah satunya mengenai besaran yang memengaruhi gaya apung benda dalam fluida utamanya pada permasalahan Hukum Archimedes. Perlu upaya pembelajaran inovatif untuk meningkatkan kemampuan siswa dalam memecahkan masalah.